2016
DOI: 10.18632/oncotarget.7656
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-30a increases tight junction protein expression to suppress the epithelial-mesenchymal transition and metastasis by targeting Slug in breast cancer

Abstract: The epithelial-to-mesenchymal (EMT) transition is a prerequisite for conferring metastatic potential during tumor progression. microRNA-30a (miR-30a) expression was significantly lower in aggressive breast cancer cell lines compared with non-invasive breast cancer and non-malignant mammary epithelial cell lines. In contrast, miR-30a overexpression reversed the mesenchymal appearance of cancer cells to result in a cobblestone-like epithelial phenotype. We identified Slug, one of the master regulators of EMT, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“…Growing evidence demonstrates that miR-30a-5p can suppress tumor cell growth in breast cancer and colorectal cancer [28, 29]. The decreased expression of miR-30a-5p was correlated with the higher clinical grading of cancer tissues (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Growing evidence demonstrates that miR-30a-5p can suppress tumor cell growth in breast cancer and colorectal cancer [28, 29]. The decreased expression of miR-30a-5p was correlated with the higher clinical grading of cancer tissues (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…It has been demonstrated that miR-30a can ameliorate hepatic fibrosis through suppressing Beclin-mediated autophagy [22]. Increasing evidence shows that miR-30a contributes to the suppression of EMT process in various cancers [23-25]. In this study, we aimed to explore whether miR-30a-mediated EMT process is involved in HSC activation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, other mechanisms potentially lead to the down-regulation of miR-30a by AR activating signal. Some studies have shown that AR and miR-30a are involved in the epithelial-mesenchymal transition in breast cancer (25)(26)(27)(28), and vimentin is a specific bridge between AR and miR-30a (26,27). Feng et al reported that AR activated by DHT potentiates the promoter activity of vimentin and upregulates vimentin expression (27), whereas Cheng et al showed that vimentin is the target of miR-30a (26).…”
Section: Discussionmentioning
confidence: 99%